A climate change projection for summer hydrologic conditions in a semiarid watershed of central Arizona. (July 2015) - Hawkins, Gretchen A.; Vivoni, Enrique R.; Robles-Morua, Agustin; Mascaro, Giuseppe; Rivera, Erick; Dominguez, Francina
Abstract: Potential climate change impacts on summer precipitation and subsequent hydrologic responses in the southwestern U.S. are poorly constrained at present due to a lack of studies accounting for high resolution processes. In this investigation, we apply a distributed hydrologic model to the Beaver Creek watershed of central Arizona to explore its utility for climate change assessments. Manual model calibration and model validation were performed using radar-based precipitation data during three summers and compared to two alternative meteorological products to illustrate the sensitivity of the streamflow response. Using the calibrated and validated model, we investigated the watershed response during historical (1990–2000) and future (2031–2040) summer projections derived from a single realization of a mesoscale model forced with boundary conditions from a general circulation model under a high emissions scenario. Results indicate spatially-averaged changes across the two projections: an increase in air temperature of 1.2 °C, a 2.4-fold increase in precipitation amount and a 3-fold increase in variability, and a 3.1-fold increase in streamflow amount and a 5.1-fold increase in variability. Nevertheless, relatively minor changes were obtained in spatially-averaged evapotranspiration. To explain this, we used the simulated hydroclimatological mechanisms to identify that higher precipitation limits radiation through cloud cover leading to lower evapotranspiration in regions with orographic effects. This challenges conventional wisdom on evapotranspiration trends and suggest that a more nuanced approach is needed to communicate hydrologic vulnerability to stakeholders and decision-makers in this semiarid region. Highlights: A climate change projection made for summer season hydrology in central Arizona. High-resolution, distributed hydrologic model outputs provide unprecedented detail. Large increases projected in precipitation and streamflow in Beaver Creek watershed. Despite higher moisture and temperature, limited future changes in evapotranspiration. Higher cloud cover and lower radiation in future explain evapotranspiration response.